STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN MOTIVASI INTRINSIK SISWA: STUDI MULTISITUS DI SDS WAWASAN NUSANTARA DAN SDN KAPUK 05 PAGI JAKARTA BARAT - Fitriyani Kosasih; Eliva Sukma Cipta; Alis Haeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Differentiated learning has become one of the key approaches in implementing the Merdeka Curriculum, emphasizing learning experiences that accommodate students' diverse readiness levels, interests, and learning profiles. However, its implementation in Islamic Religious Education (PAI) remains a challenge due to the varying characteristics and intrinsic learning motivation of students. This study aims to analyze the strategies employed by Islamic Religious Education teachers in implementing differentiated learning to enhance students' intrinsic motivation through a multisite study conducted at SDS Wawasan Nusantara and SDN Kapuk 05 Pagi, West Jakarta. The study employed a qualitative approach using a multisite research design. Data were collected through classroom observations, in-depth interviews, and documentation involving school principals, Islamic Religious Education teachers, curriculum coordinators, and students selected through purposive sampling. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while data credibility was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that Islamic Religious Education teachers implemented differentiated learning by adjusting learning content, instructional processes, learning products, and classroom environments according to students' learning needs. These strategies contributed to increased student participation, greater learning autonomy, stronger curiosity, and higher intrinsic motivation during classroom activities. Although differences were identified in instructional media utilization and learning resources between the two schools, both institutions demonstrated that teacher pedagogical competence, creativity, and student-centered instructional practices played significant roles in fostering meaningful learning experiences and strengthening students' intrinsic motivation in Islamic Religious Education.